Functionalized chitosan-based coatings for active corrosion protection - Carneiro, J.
Chitosan-based coatings were suggested in this work as a \"green\" alternative for active corrosion protection of aluminum alloys. 2-Mercaptobenzothiazole (MBT) was used here as an efficient corrosion inhibitor for AA2024. The electrochemical impedance spectroscopy has demonstrated a strong inhibiting action of MBT showing no corrosion attack even after one week in full immersion tests when MBT-loaded chitosan coatings are applied. The surface properties of the chitosan coatings were improved by chemical grafting with poly(ethylene-alt-maleic anhydride) (PEMA) and poly(maleic anhydride-alt-1-octadecene) (POMA), aiming at increasing hydrophobicity that is crucial for corrosion protection in atmospheric conditions. The high contact angles, in the range of 140 degrees, were obtained on the MBT-containing chitosan films. (c) 2013 Elsevier B.V. All rights reserved.